Discourse, organization, and the welfare state in the former east berlin - McGill, Kenneth (PoLAR: Political and Legal Anthropology Review, 2013)
In this article, I examine the statements and actions of two key informants, both of whom direct welfare programs in a district of the former East Berlin. I argue that this evidence points to a particular modality of political rationalization, which I dub organizational discourse. The entanglement of organizational discourse and governmentality are explored, as is the place of organizational discourse within both the liberal welfare state and the bygone state socialist regime.
Keywords: Discourse; Germany; Organization; Power; Welfare state; dept.ant